N-Acetylcysteine in Combination with IGF-1 Enhances Neuroprotection against Proteasome Dysfunction-Induced Neurotoxicity in SH-SY5Y Cells - Benxu Cheng; Pinki Anand; Anxiu Kuang; Feroz Akhtar; Virginia L. Scofield (Parkinson's Disease)
Ubiquitin proteasome system (UPS) dysfunction has been implicated in the development of many neuronal disorders, including Parkinson’s disease (PD). Previous studies focused on individual neuroprotective agents and their respective abilities to prevent neurotoxicity following a variety of toxic insults. However, the effects of the antioxidant N-acetylcysteine (NAC) on proteasome impairment-induced apoptosis have not been well characterized in human neuronal cells. The aim of this study was to determine whether cotreatment of NAC and insulin-like growth factor-1 (IGF-1) efficiently protected against proteasome inhibitor-induced cytotoxicity in SH-SY5Y cells. Our results demonstrate that the proteasome inhibitor, MG132, initiates poly(ADP-ribose) polymerase (PARP) cleavage, caspase 3 activation, and nuclear condensation and fragmentation. In addition, MG132 treatment leads to endoplasmic reticulum (ER) stress and autophagy-mediated cell death. All of these events can be attenuated without obvious reduction of MG132 induced protein ubiquitination by first treating the cells with NAC and IGF-1 separately or simultaneously prior to exposure to MG132. Moreover, our data demonstrated that the combination of the two proved to be significantly more effective for neuronal protection. Therefore, we conclude that the simultaneous use of growth/neurotrophic factors and a free radical scavenger may increase overall protection against UPS dysfunction-mediated cytotoxicity and neurodegeneration.